Маркетинговий потенціал як адаптаційний складник сучасного економічного розвитку підприємств - Багорка, Марія Олександрівна; Bahorka, Mariia; Юрченко, Наталія Іванівна; Yurchenko, Nataliia (Національний авіаційний університет, 2020)
У статті досліджено особливості формування маркетингового потенціалу підприємств, встановлено основні чинники, що впливають на його формування, а також представлено методи аналізу та оцінки маркетингового потенціалу. Встановлено, що маркетинговий потенціал виступає інтегрованою маркетинговою системою підприємства, в основі якої лежать маркетингова концепція управління, організація і реалізація ефективних маркетингових заходів за допомогою маркетингового інструментарію. Основу маркетингового потенціалу становлять групи елементів: комплекс маркетингу, маркетингові дослідження та маркетинговий аналіз інформації, матеріальні активи, людські ресурси, кваліфікована робота служби маркетингу. Виявлено чинники-активатори маркетингового потенціалу підприємства, які здійснюють найбільший вплив на поточний і майбутній стан системи управління маркетинговим потенціалом підприємства й дають змогу визначити стратегію його розвитку. In the article the peculiarities of formation of marketing potential of enterprises are investigated, the main factors influencing its formation are established, as well as methods of analysis and estimation of marketing potential are presented. It is established that marketing potential can not be narrowed only to the characteristics of enterprise capabilities, but is an integrated marketing system of the enterprise, based on the marketing concept of management, organization and implementation of effective marketing activities using marketing tools, system of research, collection and analysis of information, organization of strategic planning and controlling marketing activities. The basis of marketing potential is made up of groups of elements: marketing complex, marketing research and marketing analysis of information, tangible assets, human resources, qualified work of the marketing service. The groups of factors of formation and development of marketing potential of the enterprise are distinguished: external (resources of external development and their market opportunities, external marketing environment); internal (internal marketing environment that reflects the marketing material and intangible resources and opportunities of internal development of a trading company). The factors that activate the marketing potential of a trading enterprise, which exert the greatest influence on the current and future state of the management system of marketing potential of the enterprise and allow to determine the desired strategy for its development, are investigated and identified. A comprehensive approach to assessing marketing potential, incorporating quantitative metrics and qualitative characteristics, is the most accurate way to determine the most effective use of marketing potential by businesses. In order to ensure a sound assessment of the level of marketing potential of an enterprise, it is necessary to ensure the following steps: formation of a reliable and complete information base; identification of internal and external factors; development of a system of quantitative and qualitative indicators; the calculation of an integrated measure of the effectiveness of marketing potential.
Marketing potential as an adapting component of modern economic development of enterprises
Keywords: маркетинговий потенціал; marketing potential; маркетингове середовище; marketing environment; чинники впливу; factors of influence; адаптаційні можливості підприємства; adaptation capabilities of the enterprise; оцінка маркетингового потенціалу; evaluation of marketing potential